Hubungan Tingkat Pengetahuan Remaja Pria Dengan Perilaku Menjaga Kesehatan Reproduksi Di SMA Bhinneka Karya 2 Boyolali - Widodo, Aji Cahyo, Winarsih Nur Ambarwati, S.Kep., Ns., ETN., M.Kep (2016)
Adolescence is a period of transitions from early days children up to early adulthood, in the age range 10-19 years. Reproductive health is a State of physical, mental wellbeing, and social whole and not merely the absence of disease and weakness, in all matters relating to the reproductive system and functions as well as the process. Lack of knowledge about reproductive processes, the importance of maintaining cleanliness of reproductive tool, and the impact of irresponsible behavior that cause most adolescents are experiencing issues such as teens less aware of the importance of maintaining the health of their reproduction. On reproduction is not maintained clean naturally very vulnerable developing diseases caused by fungi or bacteria. Reproductive diseases can also be caused from the pattern of life or habits in adolescence. The purpose of this research is to know the relationship of man with the level of knowledge of adolescent reproductive health keep your behavior in High School Binneka Karya 2 Boyolali. The method of this research is a descriptive cross sectional approach to correlation. The sample of this research as much as 43 respondents with the techniques of sampling random sampling of the entire population. Research instrument in the form of a questionnaire sheet to find out the level of knowledge and a questionnaire to know the behavior of teenagers in High School. Analysis of Test data using the correlation of Gamma and Somer's. The research results obtained data by as much as 21 respondents (49%) have less knowledge about reproductive health, 16 respondents (37%), and 6 respondents (14%) either. Next to keep reproductive health behavior showed as many as 10% of respondents (23%) have good behavior, 22 respondents (51%) have enough behavior, and 11 respondents (26%) have less behavior. Gamma test results and Somer's retrieved values of = 0,371 with p value = 0.006 and concluded there is a relationship between the level of knowledge about reproductive health with maintaining reproductive health behavior in the age of adolescent males.